2020
DOI: 10.1287/mnsc.2019.3474
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Inventory Control with Stockout Substitution and Demand Learning

Abstract: We consider an inventory control problem with multiple products and stockout substitution. The firm knows neither the primary demand distribution for each product nor the customers’ substitution probabilities between products a priori, and it needs to learn such information from sales data on the fly. One challenge in this problem is that the firm cannot distinguish between primary demand and substitution (overflow) demand from the sales data of any product, and lost sales are not observable. To circumvent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Kok and Fisher (2007) proposed an approach to modelling the assortment decisions in which the customer may buy a substitute in the event of unavailability of his/her favourite product. Chen and Plambeck (2008) proved that inventory levels can be reduced by incorporating the learnings of substitution probabilities in the demand model. Li and Ha (2008) studied how the reactive capacity can help reduce the deviation between the supply and uncertain demand in case of substitutable products.…”
Section: Elaborate Description Of Work In the Last Two Decadesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kok and Fisher (2007) proposed an approach to modelling the assortment decisions in which the customer may buy a substitute in the event of unavailability of his/her favourite product. Chen and Plambeck (2008) proved that inventory levels can be reduced by incorporating the learnings of substitution probabilities in the demand model. Li and Ha (2008) studied how the reactive capacity can help reduce the deviation between the supply and uncertain demand in case of substitutable products.…”
Section: Elaborate Description Of Work In the Last Two Decadesmentioning
confidence: 99%
“…Netessine and Rudi (2003) discussed an optimal stocking of substitutable products using a consumer-driven substitution model under competition for a random number of products. Chen and Plambeck (2008) suggested that the inventory level of substitutable products also affects the demand and buying behaviour and hence it is important to know the demand distribution and substitution pattern. Thus store footprint can be reduced and assortment can be downsized by estimating the substitution effects in a retail basket.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, B. Chen and Chao (2020) is the only paper that studies the joint learning and optimization of inventory control problem with stock‐out substitution. In B. Chen and Chao (2020), the authors considered a one‐time or a Markov‐chain‐based stock‐out substitution, in which the substitution behavior is specified by the substitution probabilities between each pair of product and demand. Furthermore, their algorithm has predetermined separated learning and earning cycles, and in the learning cycle the algorithm allocates dedicated periods to learn the substitution probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the existing literature that mainly focuses on analyzing the structural properties and proposing efficient solution methods for the optimization problem. To the best of our knowledge, B. Chen and Chao (2020) is the only paper that studies the joint learning and optimization of inventory control problem with stock‐out substitution. In B. Chen and Chao (2020), the authors considered a one‐time or a Markov‐chain‐based stock‐out substitution, in which the substitution behavior is specified by the substitution probabilities between each pair of product and demand.…”
Section: Introductionmentioning
confidence: 99%
“…(2018), systems with fixed setup cost is studied in Yuan et al. (2019), inventory control with stockout substitution is considered in Chen and Plambeck (2008) and Chen and Chao (2020), the big data newsvendor model with feature information is studied in Ban and Rudin (2018), and learning in the dual sourcing inventory system is considered by Chen and Shi (2019). All of the studies here consider stationary environment, that is, the demand distribution stays the same throughout the planning horizon.…”
Section: Introductionmentioning
confidence: 99%